2016
DOI: 10.1111/1440-1630.12289
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapists’ perceptions of occupation in practice: An exploratory study

Abstract: Workplace expectations and limited power to influence practice are impeding graduates from authentically applying occupation in practice. Insights from recently graduated therapists about occupation have the potential to inform future directions of occupation-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 27 publications
6
40
0
1
Order By: Relevance
“…Yet occupational therapists are voicing concerns about the challenges of focusing on occupation within particular practice domains and work settings. Di Tommaso et al (2016) noted that therapists in acute services often report needing to focus on impairments rather than occupations, at least in the first instance, and that they felt this distanced them from the profession. Postmodern interpretations of occupational therapy are clearly in need of review.…”
Section: Postmodernism and The Contemporary Paradigmmentioning
confidence: 99%
“…Yet occupational therapists are voicing concerns about the challenges of focusing on occupation within particular practice domains and work settings. Di Tommaso et al (2016) noted that therapists in acute services often report needing to focus on impairments rather than occupations, at least in the first instance, and that they felt this distanced them from the profession. Postmodern interpretations of occupational therapy are clearly in need of review.…”
Section: Postmodernism and The Contemporary Paradigmmentioning
confidence: 99%
“…It is often cited that occupational therapists possess a profound understanding of the therapeutic use of occupation to enhance or enable occupational performance and engagement; however, it is clear that occupational therapists can experience difficulty with implementing occupation‐centred practice (Di Tommaso, Isbel, Scarvell, & Wicks, ; Di Tommaso, Wicks, Scarvell, & Isbel, ). Barriers to the sustained use of occupation in practice have also been researched in the Australian health‐care context, especially in acute practice settings (Di Tommaso et al, ; Wilding & Whiteford, ). Challenges include the influence of biomedical systems, the discharge‐focused nature of acute settings, the expectations of other health professionals including occupational therapists, and a lack of knowledge of occupation‐centred approaches in practice (Di Tommaso et al, , ; Wilding & Whiteford, ).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to the sustained use of occupation in practice have also been researched in the Australian health‐care context, especially in acute practice settings (Di Tommaso et al, ; Wilding & Whiteford, ). Challenges include the influence of biomedical systems, the discharge‐focused nature of acute settings, the expectations of other health professionals including occupational therapists, and a lack of knowledge of occupation‐centred approaches in practice (Di Tommaso et al, , ; Wilding & Whiteford, ). Despite this, occupational therapy scholars have encouraged a “renaissance” within occupational therapy, where occupational therapists should refocus their perspectives and practice to more closely align to the founding and central philosophies of the profession (Molineux, ; Whiteford, Townsend, & Hocking, , p. 61).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly research papers, commentaries and viewpoints which consider occupation in curriculum design and as a threshold concept have featured in the Australian literature or been written by Australian academics (Fortune & Kennedy-Jones, 2014;Rodger, Turpin & O'Brien, 2015;Tanner, 2011). A 2016 study found that occupational therapy graduates lacked confidence, and in some cases, were unwilling to implement occupation-based approaches in practice (Di Tommaso, Isbel, Scarvell & Wicks, 2016). This study highlighted the impact that university-based educators have on students' perceptions of the use of occupation in practice and found that educators predominately taught impairment focused interventions rather than occupation-based practice, leading to confusion in students.…”
Section: Introductionmentioning
confidence: 99%